91.1k views
4 votes
Multiply
-9w(-3w^8)
Simplify

1 Answer

3 votes

3^2w^9

Step by step solution :

Step 1 :

Equation at the end of step 1 :

0 - (9w • (0 - 3w8))

Step 2 :

Multiplying exponential expressions :

2.1 w1 multiplied by w8 = w(1 + 8) = w9

Multiplying exponents :

2.2 32 multiplied by 31 = 3(2 + 1) = 33

Equation at the end of step 2 :

0 - -33w9

Step 3 :

Final result :

33w9

User Abir
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.